(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Intrusion detection is an essential and important technique in research field. One of the main challengesin the security system of large-scale high-speed networks is the detection of suspicious anomalies in network traffic patterns due to different kinds of network attack. We give attacks normally identified by intrusion detection systems. Differentiation can be done in existing intrusion detection methods and systems based on the underlying computational methods used. Intrusion detection methods started appearing in the last few years. In this paper we propose an Intrusion detection method using Genetic Algorithm (GA). In this research contribution of each of above mentioned techniques will be systematically summarized and compared that will allows us to clearly define existing research challenges, and to highlight promising new research directions.